Distortion analysis of non-prismatic composite box girders with corrugated steel webs. (August 2018) - Li, Lifeng; Zhou, Cong; Wang, Lianhua
Abstract: In this study, the distortion effect of non-prismatic composite box girders with corrugated steel webs (CBGCSWs) is theoretically analysed under eccentric loads during the elastic stage. Considering the mechanical properties of corrugated steel web, a governing differential equation for distortion is derived for non-prismatic CBGCSWs. The differential equation is solved using the Newmark method to obtain the distortional warping normal stresses of angular points. The feasibility of the proposed theoretical method is validated by the finite element (FE) method. The proposed method is then applied to examine the effects of the number of diaphragms ( N ), girder length ( L ), girder width ( b ), shortest girder height ( h min ) and girder height ratio ( ξ ) on the maximum ratio of distortional warping normal stress to longitudinal bending normal stress (distortion-to-bending stress ratio, ζ ) of non-prismatic CBGCSWs. Based on the results of the parametric study, a diaphragm spacing equation is developed for determining the diaphragm spacing of non-prismatic CBGCSW bridges to reach the desired distortion-to-bending stress ratio. The presented equation can be further used as a reference to design the diaphragm spacing of this type of bridge. Highlights: A theoretical method is proposed for analysing the distortion effect of non-prismatic CBGWCSWs A governing differential equation for distortion is derived for non-prismatic CBGWCSWs Increasing the number of diaphragms or girder length can significantly reduce the distortion-to-bending stress ratio The influences of cross-sectional parameters on the stress ratio can be ignored in the case of more than 2 diaphragms A diaphragm spacing equation is developed for determining the diaphragm of non-prismatic CBGWCSWs bridges